COMPARATIVE ANALYSIS OF THE FINANCIAL PERFORMANCE OF PT ADIRA DINAMIKA MULTI FINANCE TBK AND PT ASURANSI RAMAYANA TBK - Aslam, Annisa Paramaswary (Nusantara Economics and Entrepreneurships Journals, 2025)
Financial performance is a crucial indicator in assessing a company's business sustainability, particularly in the financial services industry, such as financing and insurance, which is high in risk and requires strong capital stability. This study aims to analyze and compare the liquidity, solvency, and profitability ratios of PT Adira Dinamika Multi Finance Tbk (Adira Finance) and PT Asuransi Ramayana Tbk using financial statement data from 2021 and 2022. The research method uses a quantitative descriptive approach through financial ratio calculations according to financial analysis standards. The results show that Adira Finance has adequate liquidity but high leverage, while PT Asuransi Ramayana exhibits more stable liquidity and profitability conditions and a healthier capital structure. This comparison provides an in-depth overview of the strengths and weaknesses of both companies, which can be used as a basis for evaluation and decision-making by stakeholders.